Labour composition, productivity and skills development in the Malaysian furniture sector - Tan, Xu Chee (2019)
Labour resources are important in ensuring the successful completion of a project. The nature of furniture manufacturing in Malaysia are labor intensive. Unskilled foreign worker that dominate the workforce resulted in poor quality of project and low productivity. This study aimed to find out the current trend of labour composition, productivity and skills development, determine the reasons for foreign workers dominating the labour force and identify the challenges in recruitment and improving productivity in the Malaysian furniture sector. The study was carried out using questionnaires forms which contain selection of short and predetermined as well as Likert scale answers. The data was analyzed using average index method and frequency analysis. The result of this study show that factors that drive the employers to employ foreign workers is caused by affordable hiring cost and the challenge of improving productivity is the flip-flopping of government policy.